Exploring the Impact of Modernization on Cultural Identity in Nusantara Education - Anggia Faradina (PT. Anagata Sembagi Education, 2024)
The modernization of education in the archipelago has brought significant changes in the education system that have affected local cultural identities. This article examines the impact of the modernization process on cultural identities in educational settings in Indonesia, focusing on how changes in curriculum and teaching methods affect the understanding and preservation of traditional values. The research approach used is qualitative, involving in-depth interviews with teachers, students, and educational policy makers, as well as analysis of curriculum documents and teaching materials. The results show that the modernization of education provides opportunities to introduce global skills and contemporary knowledge, but often also ignores or reduces the role of local wisdom in the curriculum. Some schools have succeeded in integrating cultural values ​​in modern learning, but many also struggle to balance global demands and the preservation of local cultural identities. Key challenges include the lack of training for educators on local cultural integration and limited resources for teaching materials that combine tradition and modernity. This article suggests the need for a more inclusive approach in designing a curriculum that can accommodate local wisdom while meeting global standards.